METODE INVERSI AI (ACOUSTIC IMPEDANCE) UNTUK MENENTUKAN ARSITEKTUR OLIVER CARBONATE DI CEKUNGAN BROWSE, AUSTRALIA - Joko Wiyono; Suwondo Suwondo (PETROGAS: Journal of Energy and Technology, 2022)
The carbonate in the Oliver formation is a potential reservoir in Browse Basin, Australia. The limited data is the main challenge in getting better knowledge about Oliver's carbonate. In this paper, the author will generate some geophysical and geological methods to solve the problem. The aim of this study is reservoir characterization using seismic attributes, describing the internal architecture, and determining the depositional model of Oliver carbonate.This study utilized 3D seismic data and one well data. The sensitivity analysis had been generated between resistivity vs P-Impedance log. Based on cross plot analysis, AI (acoustic impedance) log can be used to differentiate porous and non-porous carbonate in Oliver formation. Vertically, based on AI volume, Oliver carbonate can be divided into 3 phases: phase-1 carbonate is indicated by carbonate build-up with low AI (high porosity), phase-2 carbonate is indicated by carbonate build up with high AI (low porosity), and phase-3 carbonate is indicated by pro grading platform with low AI (high porosity).The conclusions of this study are 1) AI inversion method can be used to know the carbonate distribution related to facies, porosity, and depositional model in Oliver formation, 2) The potential reservoirs in this study area are in carbonate build-up and pro grading platform oriented to the southeast (carbonate B, carbonate C, and carbonate D). Carbonate A with unique geometry (elbow) influenced by the current trend had potential reservoirs in carbonate build-up and pro grading platform in phase 3 oriented to SW – NE. Carbonate E is located on an extensional platform that had a potential reservoir in the carbonate build-up.